Analysis of Exchange Rate, Market Capitalization, Trading Volume Activity toward Return and Abnormal Return on Manufacturing Company (Event Study Announcement of the First Case of the Covid-19 Pandemic in Registered Automotive and Component Sub-Sector Companies on the Indonesia Stock Exchange) - Kartika Aprilia Ivani; F. Defung; Zaki Fakhroni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research was conducted on the basis of observing the condition of the capital market in Indonesia in a semi-strong form, where the market will react to an information (an announcement). If the announcement contains information signaling theory, the market will react when the announcement is received. The purpose of the study was to determine whether there is a relationship or influence of exchange rates, market capitalization, trading volume activity on stock returns and abnormal returns and to find out whether there are differences in exchange rates, market capitalization, trading volume activities on stock returns and abnormal returns around the announcement date of the case. The first covid-19 pandemic in Indonesia (before and after the announcement). This research was conducted using the event study method with a market adjusted model approach. The research sample is BEI companies (12 companies). Statistical test using multiple linear regression and different test Independent Samples Test (T-Test) with the help of IBM SPSS 22. From the results of this study it can be concluded that the exchange rate and market capitalization have a positive relationship and directly have a significant effect on returns, but trading volume activity has an insignificant negative relationship on returns and exchange rates and market capitalization have a positive and direct significant effect on abnormal returns. return, while trading volume activity has an insignificant negative relationship with abnormal returns. Besides that, that the exchange rate and market capitalization there are significant differences in returns, but trading volume activities have no significant differences on returns and exchange rates and market capitalization have significant differences on abnormal returns, and trading volume activities have no significant differences on abnormal returns.